Improved cognitive functioning in obese adolescents after a 30-week inpatient weight loss program. (August 2018) - Vantieghem, Stijn; Bautmans, Ivan; Guchtenaere, Ann; Tanghe, Ann; Provyn, Steven
Abstract Introduction Studies linked obesity with a large number of medical conditions including decreased cognitive functioning. The relation between BMI and cognition was proven in adults, but in adolescents the results are conflicting. Further, limited data are available on the impact of weight loss on cognition. This study analyzed the impact of a 30-week lasting weight loss program on cognition and determined the impact of changes in body composition and self-perceived fatigue on changes in cognition. Methods Sixty-two obese adolescents were evaluated at baseline and after 30 weeks. Stroop test (ST; selective attention), Continuous Performance Test (CPT; sustained attention) and Ray Auditory verbal learning test (RAVLT; short-term memory) were assessed. Additionally, body composition parameters and fatigue (MFI-20) were evaluated. Results Improved reaction times were found for ST and CPT after the intervention, but were independent for reductions in BMI, fat mass, fat%, and fatigue. Short memory also improved with decreased fatigue as an influencing parameter. Accuracy of ST and CPT showed no significant changes. Conclusion A 30-week lasting inpatient weight loss program improved selective attention, sustained attention, and short-term memory. Changes in body composition did not explain the improvements in cognitive functioning. Decreased fatigue resulted in improved aspects of cognition.